Teachers' Professionalism and Students' Learning Interest in Improving Students' Intelectual Intelligence in Elementary Schools in Pandeglang County - Prianti, E Nita; Prihatin, Khristina Sri (Metodik Didaktik : Jurnal Pendidikan Ke-SD-an, 2020)
This research is conducted under a fact that there is an irrelevant issue among expectation, process, and result achieved in the education. Therefore, teachers’ professionalism is highly needed to run teaching and learning activities.The purposes of this research are to 1) investigate to what extent teachers’ professionalism and students’ learning motivation can improve intellectual intelligence of the students in elementary schools in Pandeglang County, 2) investigate teachers’ efforts in improving intellectual intelligence of the students in the aforementioned schools.The method used in this research is descriptive method with qualitative approach. Meanwhile, the data source is gotten from an informant as a research subject with literature research and field research as data collection techniques by doing observation, documentation, and interview to some informants including teachers, students, and the schools’ headmasters. Next, the data isanalyzed carefully. The data show that teachers’ professionalism and students’ motivation to improve the intellectual intelligence of the students in the aforementioned schools still cannot be categorized as professional. It can be proven by the research findings where the students’ reading interest is still low. Data from 4 schools show that around 32.18% students are illiterate. The above-mentioned thing is a factor which dominates the lack of teachers’ professionalism in improving the students’ intellectual intelligence during the teaching and learning processes. It includes lack of teaching method, strategy, and skill. Therefore, the condition fails to trigger and stimulate the students’ learning interest. As a result, it can be concluded that the teacher’s professionalism is considered as less professional. KeywordTeacher’s Professionalism, Student’s Learning Interest, Student’s intellectual intelligence